Radiation non-multiply harmonics in nonlinear junction detector (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2011)
In the theoretically investigated experimentally detected the effect of negative differential resistance on the current-voltage characteristics OF the diode structures with the impact of powerful MICROWAVE radiation. Proved the expediency of usage in nonlinear junction detector high levels of power probing signal, because with a certain probability, it becomes possible to generate the object of the study of nonlinear radar own fluctuations. That in turn allows to introduce additional mode of identification mortgage devices for not the multiple harmonic in the nonlinear junction detector.